Analysis of Brand Personality and Instagram Social Media Influence on Election Decisions in the 2024 Election: As a Basis for Forming a SWOT Analysis - Syamsu Alam; Wahda; A. Rifdah Dzakiyyah Tenri Sa’na (Journal of Business Issues, 2023)
Every year, Instagram as one of social media mainstream experiences rapid development, both for its utilization in information dissemination and information retrieval. This study aims to analyze the brand personality and Instagram social media strategy as a political promotion platform for the 2024 election participants, which will later become the basis for forming a SWOT analysis. A quantitative research approach was employed in this study.. The population in this study is the entire community of South Sulawesi who fulfill the requirements as potential voters for the 2024 general election with a total of 100 respondents who are determined using the random method or commonly called a random sample from the entire population regardless of their strata. The SPSS application was utilized for analyzing the collected data.. The results of this study showed that the influence of Instagram social media on election decisions is statistically significant, or in other words, Instagram social media has an important influence in influencing election decisions. Meanwhile, Brand Personality has an influence with a sense of pride/prestigious and familiar to candidates who are new to Instagram social media. The relationship between Instagram social media and brand personality on election decisions has an important role in influencing voter decisions. These two factors work together to influence the preferences and decisions made by individuals in elections